Locating Consciousness. - Hardcastle, Valerie Gray (Advances in consciousness research ;, 1995)
Locating Consciousness argues that our qualitative experiences should be aligned with the activity of a single and distinct memory system in our mind/brain. Spelling out in detail what we do and do not know about phenomenological experience, this book denies the common view of consciousness as a central decision-making system. Instead, consciousness is viewed as a lower level dynamical structure underpinning our information processing. This new perspective affords novel solutions to a wide range of problems: the absent qualia, the binding problem, the inverted spectra, the specter of epiphenom.